Development of electrochemical biosensor: voltammetric analysis of lymphocytes and indication activation of the complement system - Pereira Oliveira, Thalyta; M Melo, Suely; J Monte, Semirames; S Silva, Adalberto; R Santos Júnior, José; Sousa Bastos, Ruan; Nayana Gomes Passos, Ionara (Seven Editora, 2023)
This work reports the development of an electrochemical biosensor after immobilization of the lymphocytes to detect the reaction between antibodies and specific HLA antigens present in the serum samples. A clean homemade gold electrode with voltammetric polycrystalline characteristics was used. Lymphocytes were immobilized and tested with positive and negative human serum and complements on the gold electrode. The experiments were carried out in a cell with three electrodes: working - gold, and reference - Ag/AgCl/sat. KCl and auxiliary - platinum. The cyclic voltammetric analyses of immobilized lymphocytes on the gold surface presented an anodic current equal to 1.78 μA at c.a. 0.50 V vs. Ag/AgCl/sat. KCl. The electrochemical responses of the serum (positive and negative) and complement do not show signs of oxidation or reduction in the potential range used. The electrodes with cells and positive serum showed the amplified current signal in the oxidation potential of the cells. The electrode was developed to verify the antigen-antibody reaction, present lymphocyte cells, and human serum samples. The electrode was qualitatively efficient when compared to the methods of flow cytometric analysis and complement-dependent cytotoxicity, being able to be used with operational and economic advantages.DOI: https://doi.org/10.56238/devopinterscie-172